AUTOMATED PROCESSING LINE FOR EFFICIENT SORTING OF WASTE RECYCLABLE MATERIALS (Balkan Journal of Applied Mathematics and Informatics, 2024)
This paper is considering the implementation of a modern automated processing line designed to enhance the efficiency of waste material sorting. With a focus on delivering products of optimal quality and quantity within defined timeframes, the research uses a comprehensive methodology integrating advanced automation techniques. Through an examination of the complex dynamics inherent in sorting processes, the research not only addresses fundamental challenges in waste management understanding but also highlights positive environmental outcomes and promotes ecological integrity. The integration of automated systems not only aims to improve productivity and staff working conditions but also aligns with the imperative of promoting a more ecologically sustainable environment. The architectural layout of the facility is strategically organized into two specialized zones, including the reception area for waste intake and sorting and preprocessing section utilizing advanced technologies. These identified zones collectively form the backbone of the facility’s infrastructure, ensuring a systematic and effective approach to waste management.